Compliance applying OHS: Are knowledge and self-regulation influence? - Hafidha Tri Kurniati; Kartika Nur Fathiyah (Research and Social Study Institute, 2021)
Occupational Health and Safety (OHS) is a work activity to prevent work accidents. Work accidents caused by workers are motivated by workers’ non-compliance at work. Compliance is known as a person’s ability to act, so that undesirable things do not happen, such as work accidents, do not happen. OHS knowledge and self-regulation affect a person’s compliance to comply with OHS. This study aimed to determine the influence of OHS knowledge and self-regulation on compliance applying OHS. The sample research involved 80 chemistry students at Universitas Negeri Yogyakarta (UNY). The results showed an effect of OHS knowledge and self-regulation on compliance applying OHS (p=0,000) with an effective contribution of 68.1%. It means that OHS knowledge and self-regulation can predict compliance applying OHS of students practising in chemical laboratories.